2018
DOI: 10.3390/ijms19071988
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Sensitivity of Adipose-Derived Stem Cells Isolated from Breast Tissue

Abstract: Within their niche, adipose-derived stem cells (ADSCs) are essential for homeostasis as well as for regeneration. Therefore, the interest of physicians is to use ADSCs as a tool for radiation oncology and regenerative medicine. To investigate related risks, this study analyses the radiation response of adult stem cells isolated from the adipose tissue of the female breast. To avoid donor-specific effects, ADSCs isolated from breast reduction mammoplasties of 10 donors were pooled and used for the radiobiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Furthermore, exposure to medium IR resulted in a strong reduction of the surviving fraction of 60% (1.0 Gy) and 80% (2.0 Gy). These results are comparable to further studies analysing the effect of IR on ADSCs, which however, used only 0.5 Gy as the smallest dose [33,37]. In contrast to IR in the high dose range with a clear dose-response relationship, after irradiation in the low and medium dose range non-linear dose-response relationships are already known from a lot of studies [38].…”
Section: Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…Furthermore, exposure to medium IR resulted in a strong reduction of the surviving fraction of 60% (1.0 Gy) and 80% (2.0 Gy). These results are comparable to further studies analysing the effect of IR on ADSCs, which however, used only 0.5 Gy as the smallest dose [33,37]. In contrast to IR in the high dose range with a clear dose-response relationship, after irradiation in the low and medium dose range non-linear dose-response relationships are already known from a lot of studies [38].…”
Section: Resultssupporting
confidence: 84%
“…For this study, ADSCs of 10 different healthy female donors were obtained from human reduction mammoplasties and pooled to avoid donor-specific effects, as well as to enhance the experimental reproducibility. In our previous work we have already demonstrated that the endpoints of radiobiological investigations in pooled ADSCs (pADSCs; N = 10) are comparable to the average of the single analysis of each donor [33]. Due to slight differences in the growth rate of ADSCs of different donors, a relatively high number of 10 donors were chosen for pooling and experiments were performed only a few doubling times after cell pooling as described before [33].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations